Avaliação da atividade biológica e farmacológica e formulação tópica de gel dental do extrato aquoso da Hyptis pectinata L. Poit - Paixão, Mônica Silveira (2012)
The Hyptis pectinata L. Poit (Lamiaceae) is an aromatic specie and, in Sergipe,occurs naturally in the wild. This study evaluated the aqueous extract phytochemical of H. pectinata (AEHP) leaves by colorimetric and HPLC ("high performance liquid chromatography") methods which detected the presence of phenols, tannins (condensed and catechins), saponins, alkaloids and free pentacyclic triterpenes. We also assessed the AEHP antibacterial, antioxidant and antinociceptive activities in vitro and in vivo the models, and also evaluated the anti-inflammatory effect of AEHP gels of 5% and 10% in experimental periodontitis in rats, comparing with doxycycline gel 10% (positive control) and vehicule gel (negative control). The antibacterial activity was tested against Citrobacter freundii, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Staphylococcus aureus and Streptococcus mutans strains by the agar diffusion technique. The growth of all bacterial strains tested was inhibited by AEHP with a diameter of zone of inhibition ranging from 15 to 36mm and the minimum inhibitory concentration values ranging from 12.5 to 1000 μg/mL-1. The results showed that the AEHP had a strong antibacterial activity against Gram positive bacteria like Staphylococcus aureus (ATCC # 25923) and Streptococcus mutans (ATCC # 27923). The AEHP reduced the DPPH radical in 72.1% with an EC50 of 14.56 μg/mL. Also inhibited 40.8% of the lipid peroxidation induced by AAPH in the TBARStest, showing activity against peroxide radicals. The orofacial antinociceptive activity was evaluated in pretreated mice with AEHP (100, 200 and 400 mg/kg, v.o.) and morphine (5mg/kg, i.p.), after receiving formalin (20 μL, 2%), glutamate (40 μL, 25 mM) and capsaicin (20 μL, 2.5 μg) causing orofacial nociception. The AEHP at all doses significantly reduced (p <0.001) the nociceptive response in the first (43-62%) and second (47-80%) phases of the formalin test. The AEHP effect (400 mg/kg) did not change in the presence of naloxone (1.5 mg/kg, i.p.), an opioid antagonist. The AEHP significantly inhibited the nociceptive response by capsaicin (23-69%, p<0.05) and glutamate (48-77%, p <0.001) at all doses. This study also examined the relationship between the activity of periodontitis and changes in body mass and alveolar bone structure after induction of Experimental Periodontal Disease (EPD) in rats with or without gel with the AEHP 5% and 10% based treatment (TTO) comparing its effects with the 10% doxycycline gel. The gels were developed in the pharmaceutical technology laboratory at the Federal University of Sergipe and immediately topically applied to the gingival area after the induction of EPD, three times daily for 11 days. The bone destruction evaluation was determined by clinical examination, histopathology and Cone Beam Computed Tomography of the experimental animals jaws (n = 36). The periodontal disease was induced by the placement of 3.0 nylon thread, involving the second molar of each animal of the fifth test group (n = 30). The control group received no ligatures (n = 6). After 11 days of periodontitis induction, the inter group comparison showed that all the groups that received ligation (group II, III, IV, V and VI) showed a decrease in mass, while the normal group (Group I - without EPD) was their body weight increased. The results of the CT scan showed healthy bone structure in group I (Normal) while the test groups showed varying degrees of bone loss, especially for the group VI (Non-Treaty),in which we observed exacerbation of the disease. The groups treated with sambacaitá 5% gel (Group II) and sambacaitá 10% gel (Group III) showed reduction in bone resorption compared to group that received 10% doxycycline gel (Group V). The histopathological analysis of the animals periodontium treated with 10% sambacaitá gel showed greater preservation of periodontal insertion and mild inflammatory infiltrate gum similar to the group treated with10% doxycycline gel. According to the results, it can be concluded that the EAHP had a strong antibacterial activity against Gram-positive bacteria. The AEHP showed antioxidant activity against the DPPH radical and against peroxide radicals. The AEHP significantly inhibited the formalin, capsaicin and glutamate-induced nociceptive response, at all doses tested. The use of gel-based AEHP 10% was able to prevent loss of body mass and bone resorption in DPE with similar effect to Doxycycline 10% (p <0.05).